2011
DOI: 10.1128/jb.00942-10
|View full text |Cite
|
Sign up to set email alerts
|

Fur Negatively Regulates hns and Is Required for the Expression of HilA and Virulence in Salmonella enterica Serovar Typhimurium

Abstract: Iron is an essential element for the survival of living cells. However, excess iron is toxic, and its uptake is exquisitely regulated by the ferric uptake regulator, Fur. In Salmonella, the Salmonella pathogenicity island 1 (SPI-1) encodes a type three secretion system, which is required for invasion of host epithelial cells in the small intestine. A major activator of SPI-1 is HilA, which is encoded within SPI-1. One known regulator of hilA is Fur. The mechanism of hilA regulation by Fur is unknown. We report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
101
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(110 citation statements)
references
References 63 publications
8
101
1
Order By: Relevance
“…By contrast, the ferric uptake regulator (Fur) does not appear to be involved in this process because an increase in iron would promote Fur dimerization and repression of its target promoters. Because one of Fur's target promoters is that corresponding to the hns gene (53), and H-NS is known to silence expression of SPI-2 genes (22), the increase in iron should increase expression of SPI-2 genes; however, we observed decreased expression (Fig. 3A).…”
Section: Discussioncontrasting
confidence: 51%
“…By contrast, the ferric uptake regulator (Fur) does not appear to be involved in this process because an increase in iron would promote Fur dimerization and repression of its target promoters. Because one of Fur's target promoters is that corresponding to the hns gene (53), and H-NS is known to silence expression of SPI-2 genes (22), the increase in iron should increase expression of SPI-2 genes; however, we observed decreased expression (Fig. 3A).…”
Section: Discussioncontrasting
confidence: 51%
“…Recently, Fur was shown to be involved in regulation of genes encoding regulators of SPI-1, a group of genes encoding all the machinery of a type three secretion system essential to the invasion of epithelial cells. Fur positively regulates HilA, the master regulator of SPI-1, via HilD (Ellermeier & Slauch, 2008;Teixidó et al, 2011) or via the repression of the histone-like protein H-NS (Troxell et al, 2011b). qPCR data confirm that hilA expression was lower in the S. Typhi fur mutant in SPI-1-inducing conditions (data not shown).…”
Section: Interaction With Epithelial Cellssupporting
confidence: 66%
“…It was previously shown that an S. Typhimurium fur mutant did not have a survival defect in murine macrophages (Garciadel Portillo et al, 1993), so it is possible that Fur has a different impact in virulence between these two serovars. However, Fur is required for the virulence of S. Typhimurium in mice (Curtiss et al, 2009;Garcia-del Portillo et al, 1993;Riesenberg-Wilmes et al, 1996;Troxell et al, 2011b;Velayudhan et al, 2007).…”
Section: Interaction With Macrophagesmentioning
confidence: 99%
See 2 more Smart Citations